Wild mushroom extracts potentiate the action of standard antibiotics against multiresistant bacteria - Alves, Maria José (2015)
Aims: The main objective of the present work was to evaluate the capacity of wild mushroom extracts to potentiate the action of standard antibiotics, through synergisms that allow a decrease in their therapeutic doses and ultimately contribute to the reduction of resistances. Methods and Results: Wild mushroom extracts were applied to different multi-resistant microorganisms (Escherichia coli, Extended-spectrum beta-lactamase-producing (ESBL) Escherichia coli and Methicillin-resistant Staphylococcus aureus (MRSA), combined with commercial antibiotics (Penicillin, Ampicillin, Amoxicillin/Clavulanic acid, Cefoxitin, Ciprofloxacin, Cotrimoxazol, Levofloxacin). Microdilution method was used to determine minimum inhibitory concentrations (MICs). The results obtained showed higher synergistic effects against MRSA than against E. coli. Mycena rosea and Fistulina hepatica were the best extracts for synergistic effects against MRSA. The efficiency of Russula delica extract against E. coli 1 (resistant to Ampicillin, Ciprofloxacin and Trimethoprim/Sulfasoxazole) and E. coli 2 (resistant to Amoxicillin/Clavulanic acid and Ampicillin) was higher than that of Leucopaxillus giganteus extract; nevertheless the latter extract exhibited better synergistic effects against ESBL E. coli. Conclusions: This study shows that, similarly to plants, some mushroom extracts can potentiate the action of antibiotics extensively used in clinical practice for Gram-positive or Gram-negative bacteria, with positive action even against multi-resistant bacteria. Significance and Impact of the Study: Mushroom extracts could decrease therapeutic doses of standard antibiotics and reduce microorganism’s resistance to those drugs.